Translating soil salinity to agricultural salt stress: Key salt-tolerance mechanisms for agrohydrologic models - Josh Gottlieb; Dvir Ochman; Cheng-Wei Huang; Jean-Christophe Domec; Nimrod Schwartz; Samantha Hartzell (iScience, 2025)
Summary: Salt stress has a detrimental impact on crop yield and survival rates, which salt-tolerant cultivars can resist through numerous adaptive mechanisms. Most models of salt stress impacts on productivity and water use employ empirical or simplified schemes to represent salt-adaptive traits. However, with an increased understanding of these physiological tolerance mechanisms and emergent measurement techniques for monitoring key salinity dynamics, the potential for developing mechanistic agrohydrological models of the soil-plant-atmosphere continuum has grown. This perspective highlights strategies for modeling salt tolerance mechanisms, including root system architecture adaptation, salt filtration, adaptation of plant hydraulics, ion compartmentalization, and stomatal responses, to improve model representation and prediction. Incorporating these mechanisms into dynamic models can help inform management strategies and biotechnological cultivation, increasing long-term salt stress resilience within salt-affected agricultural systems.